Comparative Efficacy Between Trifocal and Bifocal Intraocular Lens Among Patients Undergoing Cataract Surgery: A Systematic Review and Meta-Analysis - Zhang, Ziran; Jiang, Haiyang; Zhou, Hongwei; Zhou, Fang (Frontiers in Medicine, 2021)
The comparative efficacy of trifocal and bifocal intraocular lenses (IOLs) remained uncertain among patients undergoing cataract surgery. A systematic review and meta-analysis was performed to answer this question. PubMed, Cochrane Library and Embase were searched to capture relevant randomized controlled trials (RCTs). Visual acuity (VA) and patient’s satisfaction were regarded as primary outcomes. Secondary outcomes included residual sphere, spherical equivalence, residual cylinder, posterior capsular opacification (PCO), spectacle independence, and other complications. Statistical analysis was done using RevMan 5.2.0. A total of 9 studies (11 RCTs) with 297 participants (558 eyes) were included. Meta-analysis showed significant differences between trifocal and bifocal IOLs in the uncorrected near VA (mean difference [MD], -0.01; 95% confidence interval [Cl], -0.02 to -0.00; P = 0.03) and uncorrected intermediate VA (MD, -0.06; 95% CI, -0.10 to -0.02; P < 0.01). Trifocal IOLs were associated with decreased PCO incidence when compared to bifocal IOLs (relative risk [RR], 0.54; 95% CI, 0.31 to 0.95; P = 0.03). Trifocal IOLs may be superior to bifocal IOLs because of its improved intermediate VA and reduced incidence of PCO.